The Flexibility of Islamic Law: Criticism Toward the Intepretation of Indonesia Online Preacher on Youtube for Covid-19 - Baihaqi, Yusuf (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The existence of YouTube as a social media video platform that is easily accessible and has a wide reach, is often used to share ideas, concepts, and thoughts, especially when the Corona pandemic hit the world, preachers were no exception. This article examines the interpretations of preachers on YouTube media regarding Covid-19 that conflict with the adaptability of Islamic law.This article employs an analytical descriptive, the writer evaluates Youtobe-based online da’wah content with a focus on the interpretation of Covid-19, then analyzes it based on a flexible approach to Islamic law. A study of the online preachers' interpretations shows there is ambiguity in the opinions of online preachers about Covid-19 epidemic. This interpretation is similar to their claim that the prohibition and restrictions of the pilgrimage during the Covid-19 period were part of a conspiracy against the Islamic faith, the prohibition on congregational prayers during the Covid-19 period was seen an insult to the Islamic religion and keeping distance during congregational prayers during this time was in violation of Prophet's Sunnah. The writer states that the fundamental cause of the conflicting interpretation of Islamic law is a lack of knowledge of how flexible it is.